STRATEGI ADAPTASI USAHA INDUSTRI RUMAH TANGGA STUDI KASUS PEMBUAT GULA AREN DI DESA SIALANG JAYA ROKANHULU RIAU - Sitohang, Indra Feri; Hidir, Achmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Palm sugar is one of the brown sugar whose basic ingredients are made from the original ingredient of the original palm sugar juice, then processed into brown sugar after it is wrapped using banana leaves. Palm sugar has long been known to its presence by people who visit the road or who have long lived precisely in Sialang Jaya Village, Rokanhulu, Riau. The purpose and purpose of this study is to determine the adaptation strategies contained in the home industry business activities of palm sugar makers using a descriptive qualitative approach and the selection of informants conducted using Purposive Sampling techniques, namely the acquisition of data from informants based on criteria or limits certain restrictions. The criteria or limitations are palm sugar makers that are relatively long in producing and selling palm sugar in the area. The data collection technique used in this research is observation, interview and documentation. Conclusions from the results of this study mentioned that the adaptation strategies contained in the home industry of palm sugar making businesses consist of 2 parts, such as adaptation typology and adaptation strategies. There are 5 components of adaptation typology namely Conformity, Innovation, Ritualism, Retreatment, and Rebelion. As well as 3 parts in the adaptation strategy, in the home industry business of palm sugar makers include: Active Strategy, Passive , and Network. All of these elements are intertwined and interrelated with the business of making palm sugar, thus being able to provide a way and be able to defend their home industry business from various problems and phenomena today. Which is developed, even run to stay alive and maintain the household industry. Keyword: Adaptation Strategy, Home Industry Business